2018
DOI: 10.3347/kjp.2018.56.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Haplotype Diversity of the Apical Membrane Antigen-1 Gene in Plasmodium falciparum Populations in Thailand

Abstract: Development of an effective vaccine is critically needed for the prevention of malaria. One of the key antigens for malaria vaccines is the apical membrane antigen 1 (AMA-1) of the human malaria parasite Plasmodium falciparum, the surface protein for erythrocyte invasion of the parasite. The gene encoding AMA-1 has been sequenced from populations of P. falciparum worldwide, but the haplotype diversity of the gene in P. falciparum populations in the Greater Mekong Subregion (GMS), including Thailand, remains to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
3
9
0
Order By: Relevance
“…This was supported by Wright's F st statistics, which indicated population subdivision among the P. falciparum populations in Asia, Africa, and South America. This nding was consistent with our previous analyses wherein AMA-1 and MSP-3 sequences of P. falciparum from different endemic populations were sequenced [41,42]. In these studies, signi cant F st values were observed between P.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was supported by Wright's F st statistics, which indicated population subdivision among the P. falciparum populations in Asia, Africa, and South America. This nding was consistent with our previous analyses wherein AMA-1 and MSP-3 sequences of P. falciparum from different endemic populations were sequenced [41,42]. In these studies, signi cant F st values were observed between P.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, this could impede vaccine development since the vaccines can target only a speci c subset of antigens circulating in the malaria parasite populations [39]. Genetic analysis of the antigens expressed in the blood stage of the malaria parasite, including merozoite surface proteins and apical membrane antigens, reveal extensive polymorphisms [40,41,42]. In contrast, the sexual stage antigens are believed to be less polymorphic and their genetic diversity analyses are often neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Domain I of the AMA1 has been shown to have the highest genetic diversity (compared to the other domains) and to be the most important domain as it possesses the inhibitory epitopes of the AMA1 antigen and the cross inhibitory activities of antibodies Drew et al, 2012). The haplotype diversity of P. falciparum AMA1 has been widely studied in South East Asia and were characterized by five to six dozen SNP loci across the gene distributed mostly in the ectodomain of the AMA1 gene with domain I being the most polymorphic (Lumkul et al, 2018;Escalante et al, 2001;Polley and Conway, 2001). Our result thus confirms this polymorphic nature of domain I of the P. falciparum AMA1 antigen gene with 71.6% of the isolates having lost the restriction sites due to mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is stored in the micronemes (Srinivasan et al, 2011); it is structurally formed by 614 aa, having a 83-kDa molecular weight (Patarroyo et al, 2017a). It is differentiated into two regions; the first has a 550-aa ectodomain divided into three domains (I, II, and III) located in the N-terminal extreme, and the second, a transmembrane, intracytoplasmic region located in the C-terminal extreme (Lim et al, 2014; Lumkul et al, 2018). AMA-1 is a highly polymorphic antigen (Ouattara et al, 2010); induced Ab response mainly targets the protein’s functionally irrelevant and variable portions, thus distracting a host’s immune response (Wright and Rayner, 2014; Belachew, 2018).…”
Section: Clinical Studies Regarding Blood-stage Malaria Vaccinesmentioning
confidence: 99%